Social network interventions for dietary adherence among adults with type 2 diabetes: a systematic review and meta-analysis protocol - John Ehiri; Sarah Yeo; Halimatou Alaofè; Abidemi Okechukwu; Jean D McClelland; Waliou Amoussa Hounkpatin (BMJ Open)
Introduction Optimal adherence to recommended diets is crucial to achieving long-term glycaemic control among individuals with type 2 diabetes (T2D) individuals. However, there is limited evidence on the effectiveness of interventions that target dietary adherence through social networks. Since social networks can influence individuals’ health behaviours, it is important to thoroughly evaluate the impact of social network interventions on dietary adherence in adults with T2D. This systematic review protocol aimed to provide insights into future interventions and improve diabetes management strategies.Method and analysis PubMed, Embase, CINAHL Complete, Cochrane Central Register of Controlled Trials, ProQuest Dissertations and Theses and Google Scholar will be searched from inception to December 2023 for relevant randomised and non-randomised controlled trials of at least 3 months’ duration. In addition, studies that compared interventions involving the social networks (families, friends and peers) of adults with T2D with usual care, no intervention or an intervention with no explicit social network component will be included. Two reviewers will independently screen search outputs according to inclusion and exclusion criteria, critically evaluate the selected literature and extract data on the study setting, design, participants’ characteristics, interventions, controls, social network functions and duration of follow-up, using a standard data extraction form. Quantitative data analysis will be performed where studies are homogeneous in characteristics and provide adequate outcome data for meta-analysis. Otherwise, data will be synthesised using narrative synthesis. Finally, trials will be assessed for bias risk and overall evidence certainty using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system.Ethics and dissemination Ethical approval is not required for literature-based studies. The results will be disseminated through peer-reviewed publications.PROSPERO registration number CRD42023441223.